Pengaruh Mobilisasi Dini Terhadap Penurunan Skala Nyeri Pada Pasien Post Operasi Laparatomi di Ruangan Intensive Care Unit - Darmawidyawati Darmawidyawati; Avit Suchitra; Emil Huriani; Susmiati Susmiati; Dally Rahman; Elvi Oktarina (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
Post Laparatomy pain can be minimized by giving pharmacological and non-pharmacological therapy. Nurses has a role to reduce the pain scale of patients with independent nursing care. One of them is early mobilization therapy. This study aims to determine the effect of early mobilization of decrease in pain scale in patients post operations laparatomy. True-experimental research design and use the pretest-posttest with a control group approach. The sampling technique uses Consecutive Sampling The number of samples was 30 people using the Slovin formula. Collection of pain scale data uses C.P.O.T and pain scale collected pre and post mobilization action, then analyzed univariate and bivariate with a Mann-Whiteney U . The results of the study were obtained by p-value <0.005 there was an effect of early mobilization of the reduction in pain scale. This research suggested that early mobilization actions can be used as one of the independent nursing interventions in dealing with pain problems in post laratomy patients at Intensive Care Unit